2021
DOI: 10.9767/bcrec.16.4.12197.904-915
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Levulinic Acid Synthesis from Glucose Using Bronsted Acid Catalyst

Abstract: Glucose is one of the primary derivative products from lignocellulosic biomass, which is abundantly available. Glucose has excellent potential to be converted into valuable compounds such as ethanol, sorbitol, gluconic acid, and levulinic acid (LA). Levulinic acid is an exceptionally promising green platform chemical. It comprises two functional groups, ketone and carboxylate, acting as highly reactive electrophiles for a nucleophilic attack. Therefore, it has extensive applications, including fuel additives, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(80 reference statements)
2
6
0
Order By: Relevance
“…They found that galactose was converted almost completely in the first 5 min at a temperature of 188 °C, while the optimum yield of 40.7 mol% was achieved at 20 min. The same effect was found by Toif [30] who studied the synthesis of LA from glucose with HCl as the catalyst and by Fachri [29] who studied the synthesis of LA from fructose with H2SO4 as the catalyst. shows that at the same reaction time, the higher the acid concentration level, the higher and faster the galactose conversion.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…They found that galactose was converted almost completely in the first 5 min at a temperature of 188 °C, while the optimum yield of 40.7 mol% was achieved at 20 min. The same effect was found by Toif [30] who studied the synthesis of LA from glucose with HCl as the catalyst and by Fachri [29] who studied the synthesis of LA from fructose with H2SO4 as the catalyst. shows that at the same reaction time, the higher the acid concentration level, the higher and faster the galactose conversion.…”
Section: Resultssupporting
confidence: 75%
“…This data also implies that adding an acid catalyst to the decomposition of galactose does not lead to the desired reaction by producing more yield but to an undesired reaction for the formation of by-products. Such effect of the acid catalyst also occurred in the decomposition of fructose and glucose [16,[28][29][30], where galactose produced insoluble byproducts more than fructose and glucose did [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations